2019
DOI: 10.3390/ijms20030570
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Immunohistochemically Defined Subgroups of Non-Muscle-Invasive Papillary High-Grade Upper Tract Urothelial Carcinoma

Abstract: Immunohistochemical (IHC) staining for CK5/6 and CK20 was reported to be correlated with the prognosis of early urothelial carcinoma in a way contrary to that of advanced tumors for unknown reasons. We aimed to characterize the gene expression profiles of subgroups of non-muscle-invasive papillary high-grade upper tract urothelial carcinoma (UTUC) classified by CK5/6 and CK20 expression levels: group 1 (CK5/6-high/CK20-low), group 2 (CK5/6-high/CK20-high), and group 3 (CK5/6-low/CK20-high). Expression of group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 70 publications
(162 reference statements)
3
20
0
Order By: Relevance
“…Network and functional enrichment analyses as well as Ki-67 IHC staining demonstrated that cellular growth and proliferative functions are particularly upregulated in CK14positive papillary NMIUTUC, in accordance with previously reported high-risk phenotypes of NMIBC (13) and NMIUTUC (18) 50], which were upregulated and downregulated, respectively, in CK14-positive tumors. Dysregulation of these genes modulates proliferation, survival, migration, EMT, or metastasis of urothelial carcinoma, and other malignancies, leading to poor prognoses of these tumors.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Network and functional enrichment analyses as well as Ki-67 IHC staining demonstrated that cellular growth and proliferative functions are particularly upregulated in CK14positive papillary NMIUTUC, in accordance with previously reported high-risk phenotypes of NMIBC (13) and NMIUTUC (18) 50], which were upregulated and downregulated, respectively, in CK14-positive tumors. Dysregulation of these genes modulates proliferation, survival, migration, EMT, or metastasis of urothelial carcinoma, and other malignancies, leading to poor prognoses of these tumors.…”
Section: Discussionsupporting
confidence: 90%
“…Different studies further support the association between luminal-like type and either advanced pathological states or short survival durations in NMIBC using CK5/6 (KRT5/KRT6) and CK20 (KRT20) as surrogate protein or mRNA markers (14)(15)(16). In line with these results when studying the urinary bladder, we previously reported that papillary non-muscle-invasive upper tract urothelial carcinoma (NMIUTUC) with luminal-like, CK5/6-negative/CK20-positive, or CD44-negative/CK20positive, immunophenotypes had distinctly poor prognoses that were probably associated with altered cell adhesion and late cell cycle/proliferation functions (17,18).…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations